An Analysis of Students Mastery in Finding Verb through “A Million Dreams” Song - Pedelokta, Rahma; Masrul, Masrul; Ayu, Citra (Journal of English Language and Education, 2024)
This study was conducted to determine students' mastery in finding verbs, especially regular and irregular verbs through "A Million Dreams" song to find out how much students mastery in knowing verbs in a song. Furthermore, the method used in this study is a qualitative research method. The data of this study were collected through tests as data instruments. The population in this study were students of class X IPS 2 SMAN 1 Bangkinang in the academic year 2022/2023. The population consists of one social studies class and the sample of this study is 26 students. The results showed that a song can build students' motivation to learn English in finding verbs, especially regular and irregular verbs easily. Songs are able to facilitate students' mastery in finding verbs in a song. Thus, the writer concludes that the song "A Million Dream" can motivate students' mastery in finding verbs based on student needs and language level learning objectives. Songs in learning positive activities can develop listening skills, better understand lessons, and broaden knowledge.